"In Roars of Laughter" and "Moved to Tears" Performing the Work of Lancashire and Yorkshire Dialect Writers, c. 1850–1915. (3rd July 2022) - Walker, Andrew
ABSTRACT: The dialect literature of Lancashire and Yorkshire during the second half of the nineteenth century and early years of the twentieth century attracted many devoted readers, and has been examined by scholars interested in literature, linguistics and social and cultural history. Having given some consideration to this work the article focuses upon the performance element of this literary phenomenon. The article examines in particular the experiences of two prominent performers of their own work, Lancashire-born Edwin Waugh and Yorkshire native John Hartley. Consideration is given to the content and delivery of their performances, the nature and size of their audiences and the spaces in which these events took place. Finally, consideration is given to the fact that many performances of this dialect material were given by other people in localities far beyond the counties of Lancashire and Yorkshire, and on occasion in completely different dialects.